An Analysis of Educational Values of the Main Character in “ The Miracle Worker ” Movie - Yollanda Tiara Putri; Nurul Fitri (Universitas Batanghari Jambi, 2020)
Educational values are education in concerned with the development of the total personality of the individual intellectual, social, emotional, esthetic, moral and spiritual. This research is aimed to determining the educational values of the main characters in “ The Miracle Worker ” movie. The d2esign of this research was qualitative research. The supported data were obtained from some sources , such as books , articles , journals related to the educational values. In collecting the data , read write technique was used. The data analysis was conducted using educational values approach. The researcher found that there were nine educational values at the Miracle worker movie. Such as Never give up , Self confidence , Friendly be polite , Love , Forgiveness , Optimism , Help each other , Responsibility , Hard work. The conclusion of this research is this Movie is very good to be watch because it has many of educational values. From the story of Hellen and Mrs. Annie Sullivan, we get many very valuable lessons and the most important is our gratitude to God who has perfected the five senses.Then, the patience of a teacher who devotes all her power and makes every effort to give the best for her students. Keywords : Educational Values , Movie , The Miracle Woker.